An Investigation of Error in Velar Consonant Pronunciation Performed by University Students - Johan, Andrian Nuriza; Cahyani, Evita (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Pronunciation refers to the manner in which humans articulate the sounds of a particular language. Language proficiency is crucial for effective communication with others. In the event that our pronunciation is inadequate, we may have difficulties in being comprehended, regardless of the accuracy of our grammar and vocabulary. The objective of this research is to identify errors in the production of Velar consonants by second-semester students enrolled in the English education study program at Muhammadiyah University Purworejo during the academic year 2023/2024. This study employs a descriptive qualitative research methodology. The research focused on second semester students studying English language education. The researcher selected a sample of 20 students for the investigation. The researchers used a pronunciation test as the device to get the data. The investigation revealed a significant occurrence of mispronunciations in the final position of the /g/ sound. Students often exhibited a proclivity to replace the /k/ sound with the /g/ pronunciation, as exemplified in terms like